Targeted drug delivery strategy: a bridge to the therapy of diabetic kidney disease - Xian Chen; Wenni Dai; Hao Li; Zhe Yan; Zhiwen Liu; Liyu He (Taylor & Francis Group, 2023)
AbstractDiabetic kidney disease (DKD) is the main complication in diabetes mellitus (DM) and the main cause of end-stage kidney disease worldwide. However, sodium glucose cotransporter 2 (SGLT2) inhibition, glucagon-like peptide-1 (GLP-1) receptor agonist, mineralocorticoid receptor antagonists and endothelin receptor A inhibition have yielded promising effects in DKD, a great part of patients inevitably continue to progress to uremia. Newly effective therapeutic options are urgently needed to postpone DKD progression. Recently, accumulating evidence suggests that targeted drug delivery strategies, such as macromolecular carriers, nanoparticles, liposomes and so on, can enhance the drug efficacy and reduce the undesired side effects, which will be a milestone treatment in the management of DKD. The aim of this article is to summarize the current knowledge of targeted drug delivery strategies and select the optimal renal targeting strategy to provide new therapies for DKD.